Gill histopathology of African Catfish (Clarias gariepinus) that were fed with turmeric and infected with Aeromonas hydrophila - Bri Antoni Manalu; Morina Riauwaty; Iesje Lukistyowati (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Turmeric is an herbal plant that contains natural antibiotics and does not cause residue or danger when consumed. The active substances contained in turmeric are curcumin and essential oils. Curcumin has anti-oxidative, anti-inflammatory and antiseptic effects, turmeric has healing activity, has anti-microbial, anti-fungal activity, essential oil components, turmeric and kurlon have a broad spectrum of power in killing bacteria. Turmeric also has high antioxidant properties because it contains curcumin compounds. Aeromonas hydrophila bacteria often cause disease outbreaks with a high mortality rate (80-100%) in a short time (1-2 weeks). This bacterium causes the fish's body color to darken, the eyes are damaged and appear bulging, the scales are peeling off, all the fins are damaged, red and whitish in color, swimming gasping for air on the water surface, the gills are damaged making it difficult to breathe, the skin becomes rough and appears followed by sores. - ulcers, flatulence. This research aims to determine changes in the structure of the gill tissue of African catfish (Clarias gariepinus) due to being fed a diet containing turmeric (Curcuma domestica) and being infected with Aeromonas hydrophila. This research was conducted from May to June 2021 at the BVet Bukittinggi and at the Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine, Riau University. The treatment given was giving turmeric to the feed, namely 0.5 g/kg (P1), 0.7 g/kg (P2), 0.9 g/kg (P3). The results showed that changes in tissue structure that occurred in the gills were hyperplasia, elevated epithelium, edema and deformation of the lamellae. Based on the Histopathological Alteration Index (HAI) the best results were obtained, namely the treatment of giving turmeric 0.9 g/kg (P3) where the HAI score was 1.67 the fish gills were in normal condition, the abnormalities were still mild and could be cured